Halysis hØeg, 1932 - A problematic cyanophyceae: New evidence from the silurian of Gotland (Sweden) - Munnecke, Axel; Servais, Thomas; Vachard, Daniel (Neues Jahrbuch fur Geologie und Palaontologie Monatshefte, 2001)
Observations of new material from the Silurian of Gotland, including first studies with a scanning electron microscope, and a revision of the literature indicate that Halysis HØEG, 1932, is a morphologically highly variable, palisade-like Cyanophyceae and probably not a Codiaceae as suggested by several authors. The genus Flabellia SHUYSKY, 1973, is considered synonymous to Halysis, of which the diagnosis is emended herein. The genus is common in Ordovician to Middle Devonian reefs, reef debris limestones, and lagoonal sediments. The ecological and environmental conditions of this alga are discussed, and an anatomic reconstruction is presented.